Leadership Strategies of Madrasah Ibtidaiyah Principals to Realise Students with Islamic Character - Dewi, Triana; Imron Muttaqin (Tahta Media Group, 2024)
The madrasah head as the person in charge of educational institutions is a leader in the field of education who bears great responsibility and influence on the development of educational institutions. In line with this, the role of the madrasah principal will have a significant impact on the progress and development of education, with the aim of improving standards and human resources in the quality of education itself. This article aims to find out the strategy and implementation of the principal's leadership to build the growth of students with Islamic character, which is carried out at MI Muhammadiyah 12 Ngampel, Balong, Ponorogo. Therefore, there is a strategy in growing quality and good character students. This research is a field research with a qualitative approach, data collection through interviews, surveys, observations and documentation. This research uses qualitative methods to capture and translate phenomena and facts related to the leadership of the principal of MI Muhammadiyah 12 Ngampel. The results of this study show there are several strategies of the principal in shaping students, namely (1) being a role model for students; (2) Conducting dhuha prayer, dhuhur prayer in congregation, Tahfidz, and BTA every day; (3) implementing honesty, this is something that will be fundamental and very important in the formation of good character for students in accordance with the guidance of Islamic teachings; (4) Developing of manners and responsibilities related to behaviour, morals, and values in interpersonal interactions as well as in the context of class and society.